Cushing’s Syndrome With Nocardiosis: A Case Report and a Systematic Review of the Literature - Zhang, Da; Jiang, Yan; Lu, Lin; Lu, Zhaolin; Xia, Weibo; Xing, Xiaoping; Fan, Hongwei (Frontiers in Endocrinology, 2021)
Abstract Objective: To analyze and summarize the clinical characteristics, treatments and prognosis of Cushing’s syndrome (CS) with nocardiosis. Methods: A patient in our hospital and additional 17 patients of CS with nocardiosis in the English literature were included in this study. Clinical characteristics, laboratory data, imaging studies, treatments and prognosis were evaluated. Results: A 41-year-old man with CS was diagnosed and treated in our hospital. He had co-infections of nocardiosis and aspergillosis. Together with 17 patients of CS with nocardiosis in the English literature, 2 patients (11.1%) were diagnosed as Cushing’s disease (CD) while 16 (88.9%) were diagnosed or suspected as ectopic ACTH syndrome (EAS). The average 24hrUFC was 7587.1±2772.0 μg/d. The average serum total cortisol and ACTH (8AM) was 80.2±18.7 μg/dL and 441.8±131.8 pg/mL, respectively. The most common pulmonary radiologic findings in CT scan were cavitary lesions (10/18) and nodules (8/18). Co-infections were found in 33.3% (6/18) patients. The CS patients with co-infections had higher levels of ACTH (671.5±398.2 vs 245.5±217.1 pg/mL, P=0.047). 38.9% (7/18) patients survived through the antibiotic therapy and the treatment of CS. Patients with lower level of ACTH (survival vs mortality: 213.1±159.0 vs 554.7±401.0 pg/ mL, P=0.04), no co-infection, underwent CS surgery and received antibiotic therapy for more than 6 months, had more possibilities to survive. Conclusions: Nocardia infection should be cautioned when a patient of CS presented with abnormal chest radiographs. The mortality risk factors for CS with nocardiosis are high level of ACTH and co-infections. We should endeavor to make early etiological diagnosis, apply long-term sensitive antibiotics and aggressive treatments of CS.